OPTICAL MONITORING OF NGC4151 DURING 110 YEARS - Oknyanskij, V. L.; Metlova, N. V.; Huseynov, N. A.; Guo, Di-Fu; Lyuty, V. M. (Одеські астрономічні публікації, 2016)
We present the historical light curve of NGC 4151 for 1906–2016. The light curve (Oknyanskij and Lyuty, 2007) is primarily based on our published photoelectric data (1968–2007, about 1040 nightly mean measurements (Oknyanskij and Lyuty, 2007)) and photographic estimates (mostlyOdessaandMoscowplates taken in 1906 – 1982 (Oknyanskij, 1978, 1983), about 350 measurements). Additionally, we include all data obtained prior to 1968 (de Vaucouleurs and de Vaucouleurs, 1968; Barnes 1968; Sandage, 1967; Wisniewski and Kleinmann, 1968; Fitch et al., 1967) in total, 19 photoelectric observations from 1958–1967, were reduced by us to the same diaphragm aperture as that used in our measurements) as well as photographic data (Pacholczyk et al., 1983) (Harvard and Steward observatories' patrol plates taken in 1910–1968, about 210 measurements). The light curve includes our old and new photometrical data obtained during last years at SAI, ShAO and Weihai Observatory as well as other published data (Roberts and Rumstey, 2012; Schnülle et al., 2015). All these data were reduced to an uniform photometric system. Applying Fourier (CLEAN algorithm) we have found periodic component ~16 years in the 110 years light curve. 40 years ago about the same "period" was firstly reviled fromOdessa's photometrical data (Oknyanskij, 1977; 1978). This “period” seen in the light curve was then found independently in the spectral variability and interpreted as a case of the supermassive binary black hole (Bon et al., 2012). We interpret these circles as some accretion dynamic time.